SELECTION OF KOARMADA III PATROLING SHIP IN NORTH MALUKU SEA USING ANALYTIC NETWORK PROCESS METHOD - Supartono Supartono; Joko Purnomo; Bambang Ispri Bandono; Habiby Achmad (JOURNAL ASRO, 2020)
The geographical location of the North Maluku region and the extent of the sea that is difficult to reach by thesecurity forces to cause this area prone to illegal fishing, illegal loging, illegal entry, smuggling guns and liquor.The water traffic situation in this region is also very dense, almost every time we can see the ship that passesthrough this line especially in ALKI III, both merchant ships, passenger vessels, and vessels Fishermen can alsobe encountered there. This is what led to the province of North Maluku to be very vulnerable and provideopportunities to be utilized by people and other criminal acts to commit abuses in the North Maluku waters. Tomaximize marine security operations in North Maluku, the TNI AL at the Koarmada operations staff need tothink about and perform a mature calculation in the selection of patrol boats. This research uses the method ofAnalytic Network Process (ANP) because ANP is one method that can represent the level of interests of variousparties by considering the interconnectedness between criteria and sub-criteria that exist. The assignment ofpatrol vessels has three criteria, namely tactical, technical and economic. Processing of this selection data usingSuper decision software for ANP calculation. The results showed that the highest priority was KRI Tatihu-853 of0.851923, then the second priority for KRI Albakora-857 of 0.089943, then the third priority for KRI Madidihang-855 of 0.020778, then the fourth priority for KRI Layaran-854 by 0.016319, then fifth priority for KRI Sura-802 of0.010707, and the last sixth priority is KRI Kerapu-812 for 0.010329.Keywords: Maluku Utara, Ship Selection, ANP.